THE ROLE OF ULTRASONOGRAPHY IN ISCHEMIC BOWEL DISEASE - M. Emin CANER; Tülay ÖLÇER; Nurgül ŞAŞMAZ; Tülin ŞAHİN and M. Enver DOLAR and Alpaslan GENCER and Gülay TEMUÇİN (Turkish Journal of Gastroenterology, 2020)
-